2013
DOI: 10.1109/tmag.2012.2222634
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Serum Supplemented Cell Culture Medium on Colloidal Stability of Polymer Coated Iron Oxide and Polystyrene Nanoparticles With Impact on Cell Interactions In Vitro

Abstract: When nanoparticles interact with cells, the possible cellular responses to the particles depend on an array of parameters, in both particle and biological aspects. On the one hand, the physicochemical properties of the particles (e.g., material, size, shape, and surface charge) are known to play a key role in particle-cell interactions. On the other hand, it has been shown that prior to coming into contact with cells, nanoparticle interaction with the surrounding biological uid may lead to a change of the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…11,16,18,20,63 Admittedly, experimental assessment of the colloidal stability in the biological environment is challenging and the multitude of different CCM with a range of different components further contributes to the complexity. When NPs are delivered into cell culture media, their colloidal and chemical properties are not only altered due to the presence of proteins but also because of the high ion content (Fig.…”
Section: Colloidal Interactions In Cell Culture Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…11,16,18,20,63 Admittedly, experimental assessment of the colloidal stability in the biological environment is challenging and the multitude of different CCM with a range of different components further contributes to the complexity. When NPs are delivered into cell culture media, their colloidal and chemical properties are not only altered due to the presence of proteins but also because of the high ion content (Fig.…”
Section: Colloidal Interactions In Cell Culture Mediummentioning
confidence: 99%
“…124 On the other hand it was shown that the zeta potential of NPs is shifted to comparable negative values after incubation with supplemented CCM, independent of their intrinsic surface charge. 16,63,125 The low colloidal stability of positively charged latex NPs could therefore also be explained by bridging flocculation caused by the favorable interaction of the reactive amine groups on the particle surface with the negative surface charge of the protein. 124,126 Whether NP-protein interaction leads to the collapse or stabilization of colloidal systems has been shown to depend on an array of different parameters, both with the components of the media and the physico-chemical NP properties.…”
Section: The Role Of Proteinsmentioning
confidence: 99%
“…Let us first focus on stability of the graphene dispersions in biological solutions, such as cell culture medium, as this can govern both cellular interactions and subsequent responses. [61][62][63] Furthermore, the aggregation of nanomaterials in biological media is often associated with data misinterpretation and artifacts, 64,65 making characterisation of nanomaterials in biologically relevant media as a prerequisite for accurate interpretation of the results. Excellent colloidal stability of nanomaterials is crucial for successful biomedical applications and clinical translation.…”
Section: Stability Of Graphene In Cell Culture Mediummentioning
confidence: 99%
“…The order of this increase agrees well with the hydrodynamic radius of the BSA protein and suggests the formation of a protein monolayer adsorbed onto the surface of the Au NPs. 39,51 It is plausible that this observation was the result of two dominating but competing processes: One destabilizes the suspension, while the other balances the electrostatic screening of mobile charges 52 and preserves the aggregated or non-aggregated NPs, e.g., by the onset of a protein shell which acts as a protective layer against further aggregation. 41,53 By performing time-resolved DDLS, we are able to monitor changes in the hydrodynamic size from the point of incubation.…”
Section: Dynamic Light Scatteringmentioning
confidence: 99%